2016
DOI: 10.1016/j.bbadis.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Graded perturbations of metabolism in multiple regions of human brain in Alzheimer's disease: Snapshot of a pervasive metabolic disorder

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative disorder that displays pathological characteristics including senile plaques and neurofibrillary tangles. Metabolic defects are also present in AD-brain: for example, signs of deficient cerebral glucose uptake may occur decades before onset of cognitive dysfunction and tissue damage. There have been few systematic studies of the metabolite content of AD human brain, possibly due to scarcity of high-quality brain tissue and/or lack of reliable experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
131
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 53 publications
13
131
3
Order By: Relevance
“…From the standpoint of disease pathophysiology, the higher levels seen in AD participants also match the glucose elevation observed in diabetes mellitus,42 potentially due to their common underpinning of brain insulin resistance 43. Besides these earlier MRS findings, a recent human postmortem study also showed a dramatic glucose elevation in all brain regions of the AD specimens examined 44. Relevant concentrations of glucose in healthy individuals were previously reported as approximately 1 mmol/L in homogenous white matter, 1.1 mmol/L in gray matter,30 and 3.3 mmol/L in CSF 29, 37.…”
Section: Discussionmentioning
confidence: 60%
“…From the standpoint of disease pathophysiology, the higher levels seen in AD participants also match the glucose elevation observed in diabetes mellitus,42 potentially due to their common underpinning of brain insulin resistance 43. Besides these earlier MRS findings, a recent human postmortem study also showed a dramatic glucose elevation in all brain regions of the AD specimens examined 44. Relevant concentrations of glucose in healthy individuals were previously reported as approximately 1 mmol/L in homogenous white matter, 1.1 mmol/L in gray matter,30 and 3.3 mmol/L in CSF 29, 37.…”
Section: Discussionmentioning
confidence: 60%
“…Over the last decade, metabolomics has become one of the major “omics” tools in understanding disease pathology, identifying biomarkers, improving diagnosis and developing personalized therapy (see Botas et al, 2015; Shah et al, 2015 for reviews). In addition, brain metabolomics has been used to understand the pathology and identify potential markers for neurodegenerative diseases in both animal models and human post-mortem tissues due to the fact that metabolic changes in the brain are more likely to reflect disease etiology than those in peripheral biofluids (Pears et al, 2005; Salek et al, 2010; Graham et al, 2013; Fauvelle et al, 2015; Xu et al, 2016). In the present study, 107 small molecules were detected from 12 different brain regions and 88 of them were authentically identified.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the symptom profile of these disorders, the accumulation of urea and/or ammonia in the brain could certainly contribute to the neuropathology and symptoms of HD. Interestingly, widespread elevation of urea has also been reported in Alzheimer's disease brain tissue recently (25), suggesting that urea cycle disruption could also be a unifying pathogenic feature of neurodegenerative disease. Not all data are in agreement, however; Green and coworkers (26) identified 3.25-fold lower levels of urea in the postmortem HD striatum in the first 1H-NMR metabolomics study of HD tissue.…”
Section: Discussionmentioning
confidence: 91%